ENHANCING SCHOOL STUDENTS’ CREATIVE THINKING THROUGH HISTORICAL ART: EFFECTIVE TEACHING STRATEGIES - Dagarova Shodiya Hayotjon qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores how historical artworks can be used to foster creative thinking in school students. It examines pedagogical strategies for engaging learners with historical visual materials and their impact on imagination, critical thinking, and artistic expression. The study highlights that working with historical art promotes both cognitive and emotional development, enhancing students’ understanding of culture, history, and aesthetics. The findings offer practical recommendations for educators aiming to integrate art-based learning methods into school curricula.